2017
DOI: 10.3892/br.2017.967
|View full text |Cite
|
Sign up to set email alerts
|

A rare case of three-way complex variant translocation in chronic myeloid leukemia t(6;9;22)(p21;q34;q11): A case report

Abstract: Abstract. Philadelphia (Ph)-positive chromosome or Ph translocation has been recognized in 90-95 chronic myeloid leukemia (CML) cases worldwide. However, only 5-8% CML patients show complex variant translocations. In the present study, hematological tests for a 47-year-old female CML patient were performed to determine the hemoglobin, platelets and total leukocyte values. A FISH test was carried out to recognize the BCR/ABL gene fusion, and a cytogenetic analysis was performed. The hematological results showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
(15 reference statements)
0
6
0
Order By: Relevance
“…CML is characterized by the genetic translocation, t (9; 22) (q34; q11.2), that results in the fusion of Abelson gene (ABL1) from chromosome 9q34 with the breakpoint cluster region (BCR) gene on chromosome 22q11.2. [ 5 , 6 ] The Philadelphia chromosome translocation is observed in 90% to 95% of CML patients whereas more, complex translocations, involving a third chromosome are present in only 5% to 8% of the patients. [ 7 , 8 ] Although variant translocations might involve any chromosome, the distribution of the breakpoints is nonrandom and, usually seen at some specific chromosomal bands, including 1p36, 2p22,3p21, 4q25,5q31, 6p21, 9q22, 10q22, 11q13, 12p13, 16p13,17p13,17q21, 17q25, 19q13, 21q22, 22q12, and 22q13.…”
Section: Discussionmentioning
confidence: 99%
“…CML is characterized by the genetic translocation, t (9; 22) (q34; q11.2), that results in the fusion of Abelson gene (ABL1) from chromosome 9q34 with the breakpoint cluster region (BCR) gene on chromosome 22q11.2. [ 5 , 6 ] The Philadelphia chromosome translocation is observed in 90% to 95% of CML patients whereas more, complex translocations, involving a third chromosome are present in only 5% to 8% of the patients. [ 7 , 8 ] Although variant translocations might involve any chromosome, the distribution of the breakpoints is nonrandom and, usually seen at some specific chromosomal bands, including 1p36, 2p22,3p21, 4q25,5q31, 6p21, 9q22, 10q22, 11q13, 12p13, 16p13,17p13,17q21, 17q25, 19q13, 21q22, 22q12, and 22q13.…”
Section: Discussionmentioning
confidence: 99%
“…[ 15 ] Imatinib acts by blocking BCR-ABL gene expression and inducing apoptosis of CML cells, playing a vital role in continued survival and better quality of life. [ 5 ] Although initial response is high, therapy fails in up to 40% of patients and initial response is lost within 2 years in approximately 25% of patients with t (9;22) (q34; q11) translocation. [ 16 ] In another study, it was found that the patients with complicated differentiated disposal Ph positive CML showed a poorer prognosis after treatment with imatinib.…”
Section: Discussionmentioning
confidence: 99%
“…Around 5% to 10% of these patients show complex translocations involving a third chromosome in addition to chromosomes 9 and 22. [ 4 , 5 ] Extra Ph, +8, i(17q) and +19, have been described as the most common secondary changes (known as the major route), whereas others infrequent changes are considered the minor route. [ 6 ] Here, we report a recurrent, complicated, differentiated case of CML with t (9,22,16) (q34; q11; p13) which was treated by nilotinib, a second-generation tyrosine kinase inhibitor (TKI).…”
Section: Introductionmentioning
confidence: 99%
“…They suggested identified translocation to be associated with poor prognosis in CML patients if treated with imatinib [10]. Involvement of chromosomes 7 and 17 is also documented in literature in cases of three way translocations [11,12].…”
Section: Fig 2 Dual Color Dual Fusion Probe Depicting Atypical Patter...mentioning
confidence: 99%